Insulin dysfunction and allostatic load in bipolar disorder. (July 2011) - Brietzke, Elisa; Kapczinski, Fláávio; Grassi-Oliveira, Rodrigo; Grande, Iria; Vieta, Eduard; McIntyre, Roger S
Bipolar disorder (BD) is associated with substantial morbidity, as well as premature mortality. Available evidence indicates that ''stress-sensitive'' chronic medical disorders, such as cardiovascular disease, obesity and Type 2 diabetes mellitus, are critical mediators and/or moderators of BD. Changes in physiologic systems implicated in allostasis have been proposed to impact brain structures and neurocognition, as well as medical comorbidity in this population. For example, abnormalities in insulin physiology, for example, insulin resistance, hyperinsulinemia and central insulinopenia, are implicated as effectors of allostatic load in BD. Insulin''s critical role in CNS physiological (e.g., neurotrophism and synaptic plasticity) and pathophysiological (e.g., neurocognitive deficits, pro-apoptosis and amyloid deposition) processes is amply documented. This article introduces the concept that insulin is a mediator of allostatic load in the BD and possibly a therapeutic target.